Detection of Hydrogen Dissolved in Liquid Media: A Review and Outlook. Issue 12 (20th April 2022) - Castro-Carranza, Alejandra; Vega-Hernández, Pablo; Nolasco, Jairo C.; Ladstätter-Weißenmayer, Annette; Eickhoff, Martin; Gutowski, Jürgen
Abstract : As hydrogen continues to become rather promising for the generation of clean and sustainable energy, effective and low‐cost sensors are progressively necessary to ensure safety and efficiency of H‐based energy generation processes. Although a wide variety of hydrogen sensors for the gas phase is available, there is still a lack of devices to detect, measure, and track dissolved hydrogen. Determining its concentration is environmentally, economically, and phenomenologically relevant for applications such as offshore transport pipelines, anaerobic generation reactors, and even in electrical transformers. Herein, the technologies for sensing hydrogen dissolved in liquid media are compiled and reviewed, providing a debrief on their operation mechanisms, applications, and features, as well as an outlook of the field to be explored with new functional materials for devices applied on it. Abstract : Although a wide variety of hydrogen sensors for the gas phase is available, there is still a lack of devices to detect and track dissolved hydrogen. In this review, the technologies for sensing hydrogen dissolved in liquid media are compiled and analyzed, providing a debrief on their operation mechanisms, applications, and features, as well as an outlook of the field to be explored with new functional materials for devices applied on it.